Maternal Diet and Asthma in Children - Gulacha, Pinaz (My University, 2021)
This thesis consists of three manuscripts, which are presented in chapters 2, 3 and 4. The first manuscript (chapter 2) is a protocol for systematic review which outlines the steps used to systematically analyze the literature with regards to the primary objective of reviewing available evidence. The second manuscript (chapter 3) is the presentation of systematic review and meta-analysis in the form of a manuscript to be submitted for peer-review by fall 2020. The third manuscript (chapter 4) summarizes an analysis of CHILD study data that assesses the association of dietary patterns with infant wheeze and asthma through age 3. In chapter 5, the thesis concludes by summarizing study limitations, epidemiological implications, clinical relevance of these findings and future directions. Appendices are also included to highlight research methodology and describe comprehensively all data analyses.
Keywords: nutrition; maternal nutrition; asthma; recurrent wheeze; mediterranean diet